Kontribusi Motivasi Belajar dan Keaktifan Berorganisasi terhadap Prestasi Belajar Matematika pada Siswa SMA Al Firdaus Tahun Ajaran 2016/2017 - Indriyani, Asih, Sri Rejeki, M.Pd, M.Sc (2017)
This study has purpose to know: 1) the contribution of learning motivation on students' mathematics learning achievement. 2) the contribution from organizationactivity on students' mathematics learning achievement. 3) the ontribution oflearning motivation and organization activity on students' mathematics learningachievement. This is a descriptive quantitative study. The research samples are 30 students that takes from OSIS organization and KOMDISWA organization. Thetechnique for sampling by purposive sampling technique from the students in seniorhigh school Al-Firdaus, Pabelan. The technique of collecting data is documentationand questioner. First questioner paper has been tested to know the truth of qthe questioner paper. The technique of analyzing data using f test and t test. The result ofthe study showed that, 1) there is a contribution of learning motivation on students'mathematics learning achievement with correlation coefficient 20,188 with effectiveontribution 62,53% and relative contribution 66,,62%, 2) there is contribution oflearning motivation on students' mathematics learning achievement with correlation coefficient 18,886 with effective contribution 31,33% relative contribution 33,38%, 3) there is contribution of learning motivation and organize activity on students' mathematics learning achievement with correlation coefficient 206,376.